Non-linear system identification of the Norgaard model using NARX model / Mohd Lutfi Md Radzi - Md Radzi, Mohd Lutfi (2007)
System identification is defined as the task of inferring a mathematical model of dynamic systems based on a series of measurements collected from the system. The modelling technique is generally divided into two: linear and non-linear. The linear modelling approach has the advantage of simplicity, while the non linear approach has better ability to model more complex systems. This paper presents a non-linear system identification method the Norgaard Model, a simulation of an open-loop stable, nonlinear, continuous system.